The pedagogical aspect as a methodological component of Gramsci’s and Lenin’s thought: a reading of international hegemony and translation (PerCursos, 2024)
The objective is to answer the question: how is it possible to make a reading, a reflection on the translatability of languages involving Lenin and Gramsci analyzing the pedagogical aspect, in a broader way and no school sense, and its link with the international plan? The hypothesis is that the pedagogical aspect in its broadest and non-school sense can also be understood as a translation perspective. As such, that involves the transformations and totalizing perspectives of history and reality, covering the unequal complexity and totality relevant to the possibilities of life within states encompassing structures and superstructures as a whole, focusing on consciences, collectivities, classes and civilizations or about how worldviews and their components are received or assimilated. This unfolds into unequal and heterogeneous aspects of international hegemony. In terms of research methodology, the text was based on an analysis and a reading of texts by Gramsci and Lenin relevant to the issue at hand. Regarding the Methodology on the analytical consequences, translation in the Gramscian sense as resignification, re-reading, reception, transformation is the central point to be considered. The translation is a pedagogical aspect to capture all the complex dynamics of totality that involves numerous possibilities of transformation with regard to international hegemony and its connection with the internal scope of states.
Keywords: Gramsci; Lenin; translation; international hegemony; pedagogical aspect